Evolution of Regional Cooperation Frameworks in Eastern Europe (1990–2021). The Role of Poland as a Regional Actor - Llanos-Antczak, Anna; Śliwa, Zdzisław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2022)
Poland’s power plays an important role in building the image and international position of the country in the region. It is a good starting point to conduct a proactive policy, which gives Poland the opportunity to act on behalf or in defence of smaller regional neighbours. This, of course, can increase Poland’s own significance and potentially opens new political opportunities to contribute to the realization of its own geostrategic interests and goals; in this sense, broadening its influence. It is therefore worth analysing the roles that Poland plays within its region and find the answer to the question of how its position evolves, and to what extent regional roles have an impact on the international position and strength of the state in the European Union. The paper argues that Poland does not effectively exploit cooperation in regional organizations. Thus, its role remains below its own capabilities and it is inferior to the nation’s ambitions. Nevertheless, there is still potential to strengthen the state’s position and its international role in the European Union and beyond.

Siła Polski i jej znaczenie w regionie odgrywa ważną rolę w budowaniu wizerunku i międzynarodowej pozycji kraju. To dobry punkt wyjścia do prowadzenia aktywnej polityki, która daje Polsce możliwość działania w imieniu lub w obronie mniejszych sąsiadów. To oczywiście może zwiększyć znaczenie Polski i potencjalnie otwiera nowe możliwości polityczne dla przyczyniania się do realizacji własnych interesów i celów geostrategicznych. Warto zatem przeanalizować role, jakie Polska odgrywa w swoim regionie i znaleźć odpowiedź na pytanie, jak ewoluowała jej pozycja i w jakim stopniu role regionalne wpływają na pozycję międzynarodową i siłę państwa w Unii Europejskiej. Artykuł argumentuje, że współpraca w ramach organizacji regionalnych nie jest przez Polskę efektywnie wykorzystywana, a jej rola jest poniżej jej własnych możliwości i ambicji narodu. Niemniej jednak nadal istnieje potencjał do wzmocnienia pozycji państwa, a tym samym pozytywnego wpływania na jego rolę międzynarodową w Unii Europejskiej i poza nią.
Ewolucja form współpracy regionalnej w Europie Wschodniej (1990–2021). Rola Polski jako aktora regionalnego
Keywords: Poland; potential; Europe; region; position on international arena; Polska; potencjał; Europa; region; pozycja na arenie międzynarodowej